12-Month Results From the Unblinded Phase of the RADIANCE-HTN SOLO Trial of Ultrasound Renal Denervation - Azizi, Michel; Daemen, Joost; Lobo, Melvin D.; Mahfoud, Felix; Sharp, Andrew S.P.; Schmieder, Roland; Wang, Yale; Saxena, Manish; Lurz, Philipp; Sayer, Jeremy; Bloch, Michael J.; Basile, Jan; et al. (Jacc-Cardiovascular Interventions, 2020)
Objectives: This study reports the 12-month results of the RADIANCE-HTN (A Study of the ReCor Medical Paradise System in Clinical Hypertension) SOLO trial following unblinding of patients at 6 months. Background: The blood pressure (BP)–lowering efficacy and safety of endovascular ultrasound renal denervation (RDN) in the absence (2 months) and presence (6 months) of antihypertensive medications were previously reported. Methods: Patients with daytime ambulatory BP ≥135/85 mm Hg after 4 weeks off medication were randomized to RDN (n = 74) or sham (n = 72) and maintained off medication for 2 months. A standardized medication escalation protocol was instituted between 2 and 5 months (blinded phase). Between 6 and 12 months (unblinded phase), patients received antihypertensive medications at physicians’ discretion. Outcomes at 12 months included medication burden, change in daytime ambulatory systolic BP (dASBP) and office or home systolic BP (SBP), visit-to-visit variability in SBP, and safety. Results: Sixty-five of 74 RDN patients and 67 of 72 sham patients had 12-month dASBP measurements. The proportion of patients on ≥2 medications (27.7% vs. 44.8%; p = 0.041), the number of medications (0 vs. 1.4; p = 0.015), and defined daily dose (1.4 vs. 2.2; p = 0.007) were less with RDN versus sham. The decrease in dASBP from baseline in the RDN group (−16.5 ± 12.9 mm Hg) remained stable at 12 months. The RDN versus sham adjusted difference at 12 months was −2.3 mm Hg (95% confidence interval [CI]: −5.9 to 1.3 mm Hg; p = 0.201) for dASBP, −6.3 mm Hg (95% CI: −11.1 to −1.5 mm Hg; p = 0.010) for office SBP, and −3.4 mm Hg (95% CI: −6.9 to 0.1 mm Hg; p = 0.062) for home SBP. Visit-to-visit variability in SBP was smaller in the RDN group. No renal artery injury was detected on computed tomographic or magnetic resonance angiography. Conclusions: Despite unblinding, the BP-lowering effect of RDN was maintained at 12 months with fewer prescribed medications compared with sham.
CRIS-Team Scopus Importer:2020-12-25
Keywords: blood pressure; hypertension; renal denervation; ultrasound; variability